The role of opinion leaders in the diffusion of new knowledge : the case of integrated pest management - Savastano, Sara (Policy research working paper, 2006)
"The paper reviews the literature on the characteristics and impact of opinion leaders on the diffusion of new knowledge, concluding that there is no clear evidence on whether opinion leaders are more effective if they are similar in socioeconomic attributes to the other farmers rather than superior to would be followers. A multivariate analysis of the changes in integrated pest management knowledge in Indonesia among follower farmers over the period 1991-98 indicates that opinion leaders who are superior to followers, but not excessively so, are more effective in transmitting knowledge. Excessive socioeconomic distance is shown to reduce the effectiveness of diffusion. The paper then derives operational implications of the empirical results. "--World Bank web site